THE INFLUENCE OF EARNING MANAGEMENT, DIVIDEND POLICY, AND GROWTH OPPORTUNITY ON FIRM VALUE THROUGH INSTITUTIONAL OWNERSHIP AS AN INTERVENING VARIABLE: Case Study on Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange - Septiani, Reni (International Research of Multidisciplinary Analysis, 2024)
This study aims to test the influence of earning management, dividend policy, and growth opportunity on firm value through institutional ownership in consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. The selection of samples in this study employed the purposive sampling method, resulting in 22 companies that met the research criteria. Data were sourced from the IDX, and the analysis conducted included descriptive tests, Chow tests, Hausman tests, Lagrange Multiplier tests, classical assumption tests, t-tests, F-tests, and Sobel tests. The study's findings show that earning management and growth opportunity significantly influence firm value. Dividend policy, however, does not directly affect firm value. Based on the Sobel test results, institutional ownership does not mediate the relationship between earning management and growth opportunity to firm value but successfully mediates the relationship between dividend policy and firm value